The profile of buffalo farming in Matur District, Agam Regency, West Sumatra - Reswati; Aronal Arief Putra (Fakultas Pertanian Universitas Majalengka, 2023)
This research aimed to overview the buffalo farming business profile in Matur District and analyze its development problems. Data were obtained using the snowball sampling method by interviewing 148 buffalo farmers and observing their farming. The parameters measured were: 1) farmer demographics, 2) profile of buffalo farming business, and 3) buffalo farming practice. The results showed that the buffalo farming business in Matur District was 58.78% managed by farmers aged 25-54 years, and most of their education was elementary school (54.05%). The farmers were quite experienced in raising buffaloes (18.46 years), but the average ownership was low (1.80 heads or 0.81 Livestock Units). Most of the buffaloes' business system is a profit-sharing system (57.43%). The feed given to buffaloes was mostly natural grass (78.38%), the rearing system was carried out semi-intensively (69.59%) and intensively (30.41%), and only 54.73% of farmers provided buffalo houses. The main constraint in the buffalo farming business development in Matur District was poor farming practices, shown by the low level of technical aspects implementation (38.60%). Most buffalo mating system was natural system (96.39%). Stud limitation availability was the main constraint in buffalo reproductive management, which affected high mating costs (reached IDR 20,000-300,000/conception) and inbreeding cases (15%). Farmers' knowledge about diseases could have been higher, and the buffaloes never got vaccinated. In conclusion, the buffalo management system in Matur District was low, and thus improvement is necessary.